Pengaruh Kecerdasan Emosional, Program Kesejahteraan, dan Keseimbangan Kehidupan Kerja Terhadap Semangat Kerja - Pilawati, Lipi; Andriani, Gusti Tia; Ramadhani, Indi (Program Studi Perbankan dan Keuangan Fakultas Ekonomi Universitas Siliwangi, 2023)
The purpose of this study was to determine and analyze emotional intelligence, welfare programs, and work-life balance, as well as the influence of emotional intelligence, welfare programs, and work-life balance on the morale of non-manager organic employees of Bank BTN Tasikmalaya Branch Office. The research method used was a survey method, the data were obtained directly through questionnaires to 43 respondents taken from organic non-manager employees. Sampling using a census and the method of analysis used in this study is path analysis. Based on the results of the study, it is known that emotional intelligence is included in the high classification, welfare programs are included in the high classification, work-life balance is included in the high classification, and non-manager organic employee morale of Bank BTN Tasikmalaya Branch Office is included in the high classification. There is a significant influence between emotional intelligence, welfare programs and work-life balance on the morale of the non-organic employees of Bank BTN Tasikmalaya Branch Office.